STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGAJARKAN DOA HARIAN KEPADA SISWA DI TADIKA AL FIKH ORCHARD AWANI BANGI - Sofvia Ranti; Hasrian Rudi Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies of Islamic Religious Education teachers in teaching daily prayers to students and identify supporting and inhibiting factors in their implementation at Tadika Al Fikh Orchard Awani Bangi. This study used a qualitative approach with a descriptive approach, focusing on an in-depth understanding of the ongoing learning process. The research subjects included teachers and students, and data collection techniques included observation, interviews, and documentation. Observations were used to directly observe learning activities, interviews were conducted to obtain information from teachers regarding the strategies implemented, and documentation served as supporting data. Data analysis techniques were carried out through the stages of data reduction, data presentation, and systematic conclusion drawing. The results showed that the strategies used by teachers included habituation, repetition, role modeling, the use of learning media, and direct practice in daily activities. These strategies were deemed effective in instilling prayer habits in students from an early age. Supporting factors included teacher competence, a religious school environment, the availability of learning media, and parental support. Meanwhile, inhibiting factors identified included differences in student abilities, limited learning time, lack of habituation at home, low student concentration, and limited variety of learning media.Thus, the success of learning daily prayers is greatly influenced by appropriate strategies and support from the school and family environment. Therefore, synergy between teachers and parents is necessary to optimize ongoing learning.